Bio-synthesis of ZnO nanoparticles and their in-situ coating on cotton fabric using Azadirachta Indica leaf extract for enhanced antibacterial activity. (19th September 2022) - Ghosh, Tatan; Chattopadhyay, Amarnath; Pramanik, Subhamay; Mukherjee, Sumit; Das, Sandip; Mandal, Atis C.; Kuiri, Probodh K.
ABSTRACT: ZnO nanoparticles (NPs) of average size of 36 nm have been successfully synthesised using a low-temperature bio-synthesis method employing Azadirachta Indica leaf extract. Also cotton fabrics have been coated in-situ during synthesis of ZnO NPs for time durations of 30 , 45 , and 60 min. Amount of ZnO NPs on the cotton fabrics has been found to increase with increase in time. The bio-synthesized ZnO NPs have been found to be crystalline in structure without formation of any impurity phases. The agar diffusion method of antibacterial assay shows that ZnO NPs modified cotton fabrics is more efficient to perform antibacterial effect against Gram-negative bacteria ( Escherichia coli ) than Gram-positive bacteria ( Bacillus subtilis ). It has also been observed that better antibacterial effects are obtained for the fabric samples coated with ZnO NPs with more ageing time. That means, the modified fabrics with more NPs coated in longer deposition time show better antibacterial properties.